A multielectrode array‐based hypoxia model for the analysis of electrical activity in murine retinae. Issue 9 (10th June 2021) - Ingensiep, Claudia; Schaffrath, Kim; Denecke, Bernd; Walter, Peter; Johnen, Sandra
Abstract: Several eye diseases, for example, retinal artery occlusion, diabetic retinopathy, and glaucoma, are associated with retinal hypoxia. The lack of oxygen in the retina, especially in retinal ganglion cells (RGCs), causes cell damage up to cell degeneration and leads to blindness. Using multielectrode array recordings, an ex vivo hypoxia acute model was established to analyze the electrical activity of murine wild‐type retinae under hypoxic stress conditions. Hypoxia was induced by exchanging the perfusion with oxygen‐saturated medium by nitrogen‐saturated medium. Hypoxic periods of 0 min (control) up to 60 min were tested on the retinae of adult female C57BL/6J mice. The electrical RGC activity vanished during hypoxia, but conditionally returned after the reestablishment of conventional test conditions. With increasing duration of hypoxia, the returning RGC activity decreased. After a hypoxic period of 30 min and a subsequent recovery time of 30 min, 59.43 ± 11.35% of the initially active channels showed a restored RGC activity. The survival rate of retinal cells after hypoxic stress was analyzed by a live/dead staining assay using two‐photon laser scanning microscopy. For detailed information about molecular changes caused by hypoxia, a microarray gene expression analysis was performed. Furthermore, the effect of 2‐aminoethanesulfonic acid (taurine, 1 mM) on retinae under hypoxic stress was tested. Treatment with taurine resulted in an increase in the RGC response rate after hypoxia and also increased the survival rate of retinal cells under hypoxic stress, confirming its potential as promising candidate for neuroprotective therapies of eye diseases. Abstract : Hypoxia has an immense effect on the retina, especially on retinal ganglion cells (RGCs). It causes cell damage and results in vision loss. In this study, the electrical RGC activity under hypoxic conditions is analyzed using a multielectrode array‐based ex vivo model.